2001
DOI: 10.1002/jemt.1074
|View full text |Cite
|
Sign up to set email alerts
|

Nerve fibers innervating the cranial and spinal meninges: Morphology of nerve fiber terminals and their structural integration

Abstract: Pachymeninx and leptomeninx of cranial cavity and spine are considerably different in their collagenous fiber texture, cellular composition, vascularization, and innervation. The majority of meningeal nerve fibers terminate as free nerve endings whereas encapsulated and lamellated nerve terminals additionally occur in higher vertebrates including man. With respect to nerve fiber classification, arborization pattern, topography, and organization of the microenvironment at the termination site afferent and effer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 111 publications
(101 reference statements)
2
44
0
Order By: Relevance
“…Penfield [20], confirming and extending previous studies, showed that the trigeminal nerve is responsible for supplying the supratentorial dura in man, an observation since confirmed in animal models [1,9,2]. The trigeminal is the largest cranial nerve.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Penfield [20], confirming and extending previous studies, showed that the trigeminal nerve is responsible for supplying the supratentorial dura in man, an observation since confirmed in animal models [1,9,2]. The trigeminal is the largest cranial nerve.…”
Section: Introductionsupporting
confidence: 66%
“…The dura also contains the venous sinuses responsible for conveying the venous outflow of the brain and has an important role in controlling this venous outflow; the innervation of the human dura is most abundant around these blood vessels and sinuses [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…1A) in awake mice on a spherical treadmill during voluntary locomotion (Gao and Drew, 2014;Huo et al, , 2015aGao et al, 2015) and in response to intravenous injections of CGRP and/or sumatriptan. Although both dural vessels and pial veins drain into the sagittal sinus (Castelli and Huelke, 1965;Kerber and Newton, 1973;Fricke et al, 2001), our windows were more laterally located, such that dural vessels were clearly distinguishable from pial vessels by their superficial position relative to cerebral arteries and veins ( Fig. 1) and the lack of interconnections between the dural vasculature and cortical blood vessels.…”
Section: Resultsmentioning
confidence: 76%
“…The vasculature of the dura mater was primarily composed of arteries, which formed a network of parallel vessels ( Fig. 4C; Castelli and Huelke, 1965;Kerber and Newton, 1973;Fricke et al, 2001). Dural veins were less common than dural arteries but were present (Fig.…”
Section: Classification Of Dural Vessels Based On Dynamics and Anatomymentioning
confidence: 99%
See 1 more Smart Citation